UPAYA UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MENANGANI MASALAH PERNIKAHAN ANAK DI BANGLADESH TAHUN 2016-2019 - Regina Elisha Hutabarat; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is done to understand how a group, in this case UNICEF, involves in ending child marriage in Bangladesh. Bangladesh is one of the highest rate of child marrige country in the world, influenced by poverty and lack of education. Child marriage is followed by some big risks, young pregnancy, abuse at home, lost access of education, and abandoned by society because of social pressure. Child marriage especially happens to girl that is seen as burden n the family, because they can not do hard job. This research is based on international organisation theory, in group level analysis to understand the role of one group to another in certain issue. The datas are collected by using  qualitative methodology, most of the datas are published by official website of UNICEF, UNFPA, and Bangladesh government, books, and journals that talking about child marriage in Bangladesh.The result of this research showed that UNICEF is trying to end child marriage in Bangladesh in so many ways, including to work along with the government of Bangladesh in the making of National Action Plan to end child marriage in Bangladesh through identification, exploration, data collecting, and NAP as the result.UNICEf also work together with UNFPA in global programme to end child marriage, the result of this programme are social programmes, the making of Kishori Centre, the existence of gender promoters to increase public awareness of gender equality, social support, and public service to end child marriage in Bangadesh. Keywords: UNICEF, Bangladesh, child marriage, UNFPA, gender equality